Research of Mining Area Ecological Compensation From the Perspective of Knowledge Innovation - Xing, Qinfeng; Gang, He; Yao, Wanyan (Frontiers in Environmental Science, 2022)
an analytical model is presented to assess the ecological compensation knowledge innovation in mining areas, and the methods of factor analysis, resistance diagnosis and multiple regressions are integrated to evaluate its satisfaction in Huainan mining area. The study found that: (1) the influence of factors related to work mechanism is identical, while the influence of factors related to strategic planning and action skills is heterogeneous; (2) in terms of the relative importance of the three dimensions of work mechanism, strategic planning and action skills, their influence decreases in order. The findings can help for better improving of ecological compensation knowledge innovation, and then the following strategies are proposed to improve its knowledge innovation: firstly, the harmonious development of individual behavior and overall interests need to be realized; Secondly, the coordinated development of top-level design and adherence to faith need to be optimized; Thirdly, the interactive development guided by competence and mass entrepreneurship and innovation need to be achieved.